Experiences of Female Scientists in Research Networks in STEM fields in Public Universities in Uganda - Galenda, Safina (International Journal of Advanced Research, 2024)
Research networks are inevitable for female scientists in STEM fields, where research is carried out in teams in higher education. They promote privileged access to relevant knowledge and support from peers due to social connections. This qualitative study set out to explore the experiences of female scientists in research networks in STEM fields in public universities in Uganda. The study's population encompassed female scientists in research networks in STEM fields in public universities in Uganda that included Makerere University, Mbarara University of Science and Technology, Gulu University and Busitema University. In respect to this study, my participants were selected in the STEM fields in public universities in Uganda. Female scientists in research networks were selected in the hard pure and hard applied disciplines as classified by Becher and Biglan's typology of academic disciplines of 1973. From their classification of academic disciplines, the STEM fields belong to the hard pure and hard applied disciplines. This study was anchored on the existential phenomenology by Martin Heidegger in the interpretive worldview. Both semi-structured interviews and document check data collection methods were used in this study. A sample size comprising of eight female scientists in research networks in STEM fields in public universities in Uganda were interviewed. Data were thematically analysed where clustering into catergories and emerging sub-themes were developed to form themes. This study concludes that those female scientists in research networks had positive experiences such as funding, networking, research skills, career growth, conferences, mentoring, and negative experiences like hectic schedules and delayed funding. The findings that emerged from the study indicated positive experiences with the research networks, which enabled them to win research grants, projects, and postdoctoral fellowships successfully. Those female scientists believed that their inter-institutional, national, regional, and international interactions and engagements spurred excellent opportunities for them in their universities. This was because they were exposed to top-notch scientists in their disciplines. This study, therefore, recommends to the management of public universities in Uganda to establish formal research networks and strengthen the existing informal research networks